(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This study presents one approach to investing in the financial markets using a decision theory point of view, where the main decision is to choose an investment portfolio, based on economic indexes, in order to predict future investments based on historical data, which minimizes the risk involved. This examination proposes a model to handle the portfolio determination issue. The accompanying areas present the components of the model created. The probability distributions can be updated and they will incorporate more information into the model in future decisions. Surprisingly the actions that were compiled for more than one asset were not recommended by the model. We believe this occurs due to Bayesian Risk Analysis being based on the value of the losses expected. Perhaps a new element of variance of the portfolios can be incorporated into the Decision Portfolio Investment Selection model.